2000
DOI: 10.1212/wnl.54.6.1331
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI correlates of real and imagined tool-use pantomimes

Abstract: Pantomiming the use of tools is associated with activation of the left intraparietal cortex and dorsolateral frontal cortex. The left intraparietal cortex may store the representations of tool-use formulae, whereas the dorsolateral frontal cortex activation may reflect the switching between innervatory motor programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
108
2
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(131 citation statements)
references
References 18 publications
20
108
2
1
Order By: Relevance
“…In previous neuroimaging studies, researchers asked participants to make pantomimes with both right and left hands and showed that the left-lateralized parietal and premotor networks are activated for both dominant and non-dominant hands (Moll et al 2000;Johnson and Grafton 2003;Johnson-Frey et al 2005). However, with a conventional subtraction method based on mass univariate analysis, it cannot be decided whether there is left IPL, which is consistent with the lesion cases of IMA (Buxbaum et al 2007;Binkofski and Buxbaum 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous neuroimaging studies, researchers asked participants to make pantomimes with both right and left hands and showed that the left-lateralized parietal and premotor networks are activated for both dominant and non-dominant hands (Moll et al 2000;Johnson and Grafton 2003;Johnson-Frey et al 2005). However, with a conventional subtraction method based on mass univariate analysis, it cannot be decided whether there is left IPL, which is consistent with the lesion cases of IMA (Buxbaum et al 2007;Binkofski and Buxbaum 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The difference between their study 20 results and the current results is that they showed almost an equal importance in the classification accuracy of bilateral PPC, whereas our results showed left-hemispheric dominance. Considering that a number of previous neuroimaging studies on tool use (Moll et al 2000;Choi et al 2001;Rumiati et al 2004;Fridman et al 2005;Johnson-Frey et al 2005;Imazu et al 2007) also showed left-hemisphere dominance, this discrepancy may be a result of the movement types. The difference in neural substrates between simple manual actions and tool use is also supported by the fact that IMA patients showed no impairments in visually guided grasping or reaching (Haaland et al 1999).…”
Section: Iplmentioning
confidence: 92%
See 1 more Smart Citation
“…Naming [Grafton et al, 1997;Martin et al, 1996] or recognition [Grafton et al, 1997;Perani et al, 1995] of man-made tools similarly activates left frontal regions. Finally, strongly left-sided activations in frontal areas are observed in two studies in which tool-use gestures are compared with simple movements during real or imagined pantomimes upon verbal command [Choi et al, 2001;Moll et al, 2000].…”
Section: Action Semantic Systemmentioning
confidence: 92%
“…Based on dissociations in brain-damaged patients, Goodale and Milner (1992) and Milner and Goodale (1995) suggested that pantomime was more dependent on the ventral stream of visual processing (temporal lobe "what" pathway) and less dependent on the dorsal stream (parietal lobe "where and how" pathway) than object use. However, one fMRI suggested that parietal cortex is critical for pantomimed tool use, as the primary difference between pantomiming and reproducing a meaningless gesture sequence was in parietal rather than temporal regions (Moll et al, 2000). Not in dispute is the fact that, in both healthy subjects and patients, the actions performed during pantomimed and real-object use are not identical (Goodale et al, 1994;Laimgruber et al, 2004;Milner and Goodale, 1995;Westwood et al, 2000).…”
Section: Varieties Of Action: Pantomime Versus Interactions With Realmentioning
confidence: 99%